Duodenal Infusions of Starch with Casein or Glutamic Acid Influence Pancreatic and Small Intestinal Carbohydrase Activities in Cattle. Issue 4 (25th December 2019) - Trotta, Ronald J; Sitorski, Leonardo G; Acharya, Subash; Brake, Derek W; Swanson, Kendall C
ABSTRACT: Background: Small intestinal starch digestion in ruminants is potentially limited by inadequate production of carbohydrases. Previous research has demonstrated that small intestinal starch digestion can be improved by postruminal supply of casein or glutamic acid. However, the mechanisms by which casein and glutamic acid increase starch digestion are not well understood. Objectives: The objective of this experiment was to evaluate the effects of duodenal infusions of starch with casein or glutamic acid on postruminal carbohydrase activities in cattle. Methods: Twenty-two steers [mean body weight (BW) = 179 ± 4.23 kg] were surgically fitted with duodenal and ileal cannulas and limit-fed a soybean hull–based diet containing small amounts of starch. Raw cornstarch (1.61 ± 0.0869 kg/d) was infused into the duodenum alone (control), or with 118 ± 7.21 g glutamic acid/d, or 428 ± 19.4 g casein/d. Treatments were infused continuously for 58 d and then steers were killed for tissue collection. Activities of pancreatic (α-amylase) and intestinal (maltase, isomaltase, glucoamylase, sucrase) carbohydrases were determined. Data were analyzed as a randomized complete block (replicate group) design using the GLM procedure of SAS to determine effects of infusion treatment. Results: Duodenal casein infusion increased ( P < 0.05) pancreatic α-amylase activity by 290%. Duodenal glutamic acid infusion increased ( P < 0.03) duodenal maltase activity by 233%. Duodenal casein infusion increased jejunal maltase ( P  = 0.02) and glucoamylase ( P  = 0.03) activity per gram protein by 62.9% and 97.4%, respectively. Duodenal casein infusion tended to increase ( P  = 0.10) isomaltase activity per gram jejunum by 38.5% in the jejunum. Sucrase activity was not detected in any segment of the small intestine. Conclusions: These results suggest that small intestinal starch digestion can be improved in cattle with increased small intestinal flow of casein through increases in postruminal carbohydrase activities.